The study of the lives and activities of Armenian spiritual leaders as an direction in Armenian studies (according to the example of Gevorg E Surenyants) - Amirjanyan , Hasmik (History and Culture, 2025)
Today, in the field of studying the history of the Armenian Church, a direction is gradually emerging that is dedicated to illuminating the lives and activities of Armenian spiritual leaders, especially the Catholicoses of all Armenians. The primary foundation for such research consists of letters, reports, and records of spiritual figures.The publication of documents, as well as unpublished memoirs, significantly contributes to and facilitates the complete restoration of the lives and activities of Armenian spiritual leaders. In these works, the activities of the Catholicoses, who assumed political functions in the absence of state power, are particularly emphasized, as they essentially represent manifestations of both the internal and external policies of the country. By engaging in economic, social, cultural, and educational activities within the country, they contributed to the development of all these spheres.The article presents the role of a spiritual leader in various spheres of the country's life through the example of Catholicos of All Armenian Gevorg Surenyants.Thus, by studying the history of various periods in the lives and activities of the Catholicoses and spiritual leaders of Armenia, we are essentially exploring Armenian history and developing Armenian studies, while translating these materials into other languages expands the horizons of Armenian studies.
Keywords: Armenian studies; spiritual leaders; Catholicos of All Armenians; documents; Gevorg Surenyants; The Armenian Apostol Church; reforms